Corporate Social Responsibility: Three Key Approaches - Windsor, Duane (Journal of Management Studies, 2006)
abstract Corporate social responsibility remains an embryonic and contestable concept. This paper assesses three key approaches and offers a perspective gauging little prospect of theoretical synthesis. Ethical responsibility theory advocates strong corporate self‐restraint and altruism duties and expansive public policy strengthening stakeholder rights. Economic responsibility theory advocates market wealth creation subject only to minimalist public policy and perhaps customary business ethics. These two viewpoints embed competing moral frameworks and political philosophies. Any theoretical synthesis must discover some subset of ethical principles yielding corporate competitive advantage. Corporate citizenship language invokes a political metaphor providing neither true intermediate positioning nor theoretical synthesis. Two conflicting interpretations abandon responsibility language without adopting the economic viewpoint. An instrumental citizenship interpretation expands philanthropy as a strategic lever for increasing corporate reputation and market opportunities while retaining managerial discretion. An ideal citizenship interpretation restates ethical responsibility into voluntarism language intended to influence managerial discretion concerning universal human rights.